Design and Evaluation of Acceptance of a Web-Based System at Nurul Hidayah Islamic Boarding School - Yulianingsih, Sri; Pamungkas, Bayu (Jurnal Accounting Information System (AIMS), 2026)
The design and development of a web-based information system to improve the quality of service and education at Nurul Hidayah Islamic Boarding School represented a strategic effort to utilize information technology in enhancing administrative efficiency and information accessibility. The system was developed to address problems related to ineffective information dissemination and the manual registration process for new students. The web-based application, developed using the Waterfall method, enabled online student registration and provided faster and more accurate access to educational information. System development involved requirements analysis, Unified Modeling Language design, interface and backend implementation, and system testing. To evaluate the effectiveness of the developed system, user acceptance was assessed using User Acceptance Testing based on a five-point Likert scale questionnaire involving 15 system users. The evaluation focused on system usability, ease of use, information clarity, system efficiency, and user satisfaction. The evaluation results showed an overall average acceptance score of 4.39, indicating a high level of user acceptance. These results demonstrated that the system was capable of improving administrative efficiency and supporting educational services in a more structured and effective manner.